Escherichia coli BW25113 Competent Cells Prepared Using a Simple Chemical Method Have Unmatched Transformation and Cloning Efficiencies - Yang, Yuqing; Yu, Qiaoli; Wang, Min; Zhao, Rui; Liu, Huaiwei; Xun, Luying; Xia, Yongzhen (Frontiers in Microbiology, 2022)
Escherichia coli recA- strains are usually used for cloning to prevent insert instability via RecA-dependent recombination. Here, we report that E. coli BW25113 (recA+) competent cells prepared by using a previously reported transformation and storage solution (TSS) had 100-fold or higher transformation efficiency than the commonly used E. coli cloning strains, including XL1-Blue MRF’. The cloning success rates with E. coli BW25113 were 440 to 1267-fold higher than those with E. coli XL1-Blue MRF’ when several inserts were assembled into 4 vectors by using a simple DNA assembly method. The difference was in part due to RecA, as the recA deletion in E. coli BW25113 reduced the transformation efficiency by 16 folds and cloning success rate by about 10 folds. However, the transformation efficiency and the cloning success rate of the recA deletion mutant of E. coli BW25113 are still 12- and >48-fold higher than those of E. coli XL1-Blue MRF’, which is a commonly used cloning strain. The cloned inserts with different lengths of homologous sequences were assembled into four vectors and transformed into E. coli BW25113, and they were stably maintained in BW25113. Thus, we recommend using E. coli BW25113 for efficient cloning and DNA assembly.